Grade 13 commerce students’ perceptions on English language learning at a government school in Nintavur Educational Division - Rafee, M.H.M.; Safeek, N.M.M. (Muallim Journal of Social Science and Humanities, 2024)
This study aims to comprehensively understand Grade 13 Commerce students' perceptions of English language learning at a government school in the Nintavur Educational Division. The research identifies challenges students face, evaluates the effectiveness of learning resources and teaching aids, and assesses overall learning experiences and teachers' attitudes. Employing a mixed-methods approach, the study integrated quantitative and qualitative data collection, involving 74 students, two English teachers, and educational stakeholders, including the Principal and In-Service Advisor (ISA). Data were gathered through structured questionnaires, semi-structured interviews, focus group discussions, and classroom observations. Quantitative analysis revealed students' fear of making mistakes, lack of confidence, and concerns about pronunciation as significant barriers to learning English. The effectiveness of learning resources was met with mixed opinions, indicating uncertainty about their impact. The study also highlighted dissatisfaction with current teaching methods, with a noted disconnect between teaching practices and students' needs. Chi-Square analysis showed no significant gender differences in perceptions of learning experiences or teachers' attitudes. Qualitative insights from interviews and observations suggested gaps in textbooks and a need for more interactive and practical teaching approaches. The study concludes that addressing emotional barriers, improving teaching resources, and enhancing teacher training are critical for advancing English language education. A multifaceted approach, incorporating better pedagogical strategies, relevant resources, and supportive learning environments, is essential for overcoming the identified challenges and improving students' English language proficiency.
Keywords: commerce students' perceptions; English speaking ability; ESL; government school